Molecular Diversity and Chemical Composition Among Induced Mutation Lines of Pogostemon cablin (Blanco) Benth. Using RAPD and ISSR Marker. Issue 2 (4th March 2022) - Pandey, Sudin Kumar; Baruah, Joyashree; Paw, Manabi; Sarma, Neelav; Begum, Twahira; Saikia, Samarjit; Lal, Mohan
Abstract: Pogostemon cablin, also known as Patchouli is an essential oil yielding plant with high medicinal properties and having great value for its unique essential oil component. The essential oil is widely used in flavor and fragrance industries. The objective of the present study is to evaluate molecular diversity among mutation treated progeny using RAPD (Randomly amplified polymorphic DNA) and ISSR (Inter Simple Sequence Repeat) markers. The essential oil composition which was analyzed using GC/MS showed patchouli alcohol as major compound, followed by sabinene, (-)β-elemene, α-Guaiene, α-humulene, caryophyllene oxide and viridiflorol in the studied lines. Total 44 RAPD and 34 ISSR primers were used for 41 mutated selected lines, which showed an average polymorphic percentage of 70.1% and 58.14% respectively. Genetic parameters studied by both markers systems were found to be more or less similar. Analysis of molecular variance showed 45% variation among population and 55% within the population by RAPD marker, while ISSR marker showed 36% variation among population and 64% within population. Cluster analysis using both markers grouped the lines into three main clusters and Principal Component Analysis (PCA) plot also supported cluster analysis data. The present study will be helpful in conservation of patchouli germplasm, their characterization and in future breeding programme.